Shaun Hill: Cooking at the Merchant House - Davidson, Alan E (Petits Propos Culinaires, 2025)
Shaun Hill: Cooking at the Merchant House. Conran Octopus, London, 2000: ISBN 1-84091-131-X: 192 pp., colour photos, h/b, £20.